(untitled) (Communications in Computational Chemistry, 2025)
Expanded porphyrins serve as promising candidates for MRI contrast agents and sensitizers in photodynamic therapy. In this study, we theoretically designed a series of expanded porphyrins incorporating thiophene and selenophene moieties to investigate their optoelectronic properties. Density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations were performed to assess their aromaticity, stability, and photophysical characteristics. Our results reveal that all designed molecules exhibit superior optoelectronic performance, with enhanced aromaticity compared to conventional porphyrins. The absorption spectra of the molecules closely resemble that of porphyrins, suggesting potential applicability in related biomedical and photonic applications. Notably, molecule 4, featuring both a thiophene moiety and a conventional selenophene ring, demonstrates the highest stability, an increased energy gap highest between occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), and a planar geometry, leading to strengthened aromaticity. These findings provide valuable insights for the rational design of next-generation porphyrin-based materials.